A multicenter, open-label study for efficacy and safety evaluation of anagrelide in patients with treatment-naïve, high-risk essential thrombocythemia as a primary treatment - Byun, Ja Min; Kim, Ho Young; Nam, Seung-Hyun; Shin, Ho-Jin; Song, Seulki; Park, Jinny; Han, Sang Hoon; Park, Yong; Yuh, Young Jin; Mun, Yeung-Chul; Do, Young Rok; Sohn, Sang Kyun; et al. (Frontiers in Oncology, 2022)
As the discussion of first-line anagrelide treatment is ongoing, we aimed to prospectively examine the efficacy and safety of anagrelide in cytoreduction therapy-naïve high risk essential thrombocythemia (ET) patients in Korea. Seventy patients from 12 centers were treated with anagrelide monotherapy for up to 8 weeks, followed up until 24 months. At week 8, 50.0% of the patients were able to achieve platelet < 600 x 109/L, and by 12 months, 55/70 (78.6%) patients stayed on anagrelide, and 40.0% patients showed platelet normalization. 14 patients required additional hydroxyurea (HU) for cytoreduction. The median daily dose of needed HU was 500mg (range 250mg – 1500mg). The efficacy was independent of the somatic mutation status. There were 4 thromboembolic events and 7 bleeding events during the follow-up period. The most common adverse events associated with anagrelide use were headache, followed by palpitation/chest discomfort, edema and generalized weakness/fatigue. 7 patients wished to discontinue anagrelide treatment due to adverse events (3 due to headache; 2 due to edema; 1 due to palpitation and 1 due to skin eruption). All in all, first-line anagrelide treatment showed a favorable response with tolerable safety profiles regardless of somatic mutation status.